Highway traffic monitoring and data quality - Dalgleish, Michael (Artech House ITS library., 2008)
This unique resource gives you a hands-on understanding of the latest sensors, processors, and communication links for everything from vehicle counts to urban congestion measurement. Moreover, you learn statistical techniques for quantifying data accuracy and reducing uncertainty in both current system state assessments and future system state forecasts.